Використання математичних моделей щодо дослідження політичного ризику - Демчук, Д. В.; Демчук, Д. В.; Demchuk, D. (My University, 2013)
In this article analysis of possibility of mathematical models application for research of political risk stages is given. In particular, experience of application of mathematical approaches for the analysis of political situation in regions in the period of the USSR is studied. Also application of cumulative method for prognostication of political situations in the aspect of risk of appearance and development of instability is analysed.
Демчук Д. В. Використання математичних моделей щодо дослідження політичного ризику / Д. В. Демчук // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 66-74.
Keywords: політичний ризик; дослідження стадій політичного ризику; математичні моделі у дослідженні стадій політичного ризику; политический риск; исследование стадий политического риска; математические модели в исследовании стадий политического риска; political risk; research stages of political risk; Mathematical models in the study of the stages of political risk